Retrospective and prospective of the hydrogen supply chain: A longitudinal techno-historical analysis. (4th December 2020) - Khalilpour, Kaveh R.; Pace, Ron; Karimi, Faezeh
Abstract: The objective of this study was to investigate the evolution of hydrogen research and its international scientific collaboration network. From the Scopus database, 58, 006 relevant articles, published from 1935 until mid-2018, were retrieved. To review this massive volume of publication records, we took a scientometric network analysis approach and investigated the social network of the publication contents based on keywords co-occurrence as well as international collaboration ties. An interesting observation is that despite publications on hydrogen occurring since 1935, the growth of this research field ignited with the Kyoto Protocol of 1997. The publication profile reveals that more than 93% of the existing records have been published over the last two decades. More recently, the accelerated growth of renewables has further motivated hydrogen research with almost 36, 000 academic records having been indexed from 2010 till mid-2018. This accounts for 62% of the total historical publications on hydrogen. The conventional hydrogen production pathway is fossil fuel-based, involving fossil fuel reforming for synthesis gas generation. The keyword analysis also shows a paradigm shift in hydrogen generation to renewables. While all components of hydrogen supply chain research are now growing, the topic areas of biohydrogen and photocatalysis seem to be growing the fastest. Analysis of international collaboration networks also reveals a strong correlation between the increase of collaboration ties on hydrogen research and the publications. Until the 1970s, only 25 countries had collaborated, while this has reached 108 countries as of 2018, with over 17, 500 collaboration ties. The collaborations have also evolved into a substantially more integrated network, with a few strong clusters involving China, the United States, Germany, and Japan. The longitudinal network evolution maps also reveal a shift, over the last two decades, from US-Europe centred technology development-interaction to a world in which Asian economies play substantial roles. Graphical abstract: Image 1 Highlights: Investigation of the evolution of hydrogen research and its international scientific collaboration network. Scientometric analysis to study the social network of the publication contents. 93% of the publications have appeared after the Kyoto Protocol (1997) and 62% have appeared since 2010 (the era of renewables revolution). The topic areas of biohydrogen, photo-catalysis, and water splitting are growing the fastest, implying the strong shift toward renewable hydrogen. A shift, over the last two decades, from US-Europe centred technology development-interaction to Asian economies.